Improving a Car Dealership’s Communications through the Comunicom Direct Active Communication System - Cezar CALUSCHI (Revista de Management Comparat International)
The automotive industry is a trendsetter in communications, as it employs the latest technologies and communications techniques in order to adapt to the clients’ needs. During 2006 to 2012 I implemented an innovative direct active communication system within a local Romanian Toyota dealership; the system called Comunicom (registered mark) aims to streamline the organization’s communication processes with the dealership’s target groups. Comunicom is a matrix-based system adding communications applications to marketing. By combining data research & storing technologies and communications technologies with analyses and dynamic management matrices based on the organization’s relations with clients, the system proves to be an efficient technology application for marketing communications. The implementation was successful, leading to significant improvements in the company’s marketing communications mix and its commercial results. Once implemented, Comunicom was updated continuously and used over more than 5 years, leading to the same excellent commercial results.